2005
DOI: 10.1210/en.2004-0882
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Directly Stimulates Cortisol Secretion by Human Adrenal Cells by a Cyclooxygenase-Dependent Mechanism

Abstract: Activation of the hypothalamo-pituitary-adrenal axis by bacterial lipopolysaccharide (LPS; endotoxin) is well documented, although there has been uncertainty about whether LPS exerts a direct effect at the level of the adrenal. The present study found that LPS caused a dose-dependent stimulation of basal cortisol secretion by the human adrenocortical cell line, NCI-H295R, without affecting aldosterone. The expression of both Toll-like receptor 2 (TLR2) and TLR4 was demonstrated in these cells, and the specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 26 publications
6
50
1
Order By: Relevance
“…Surprisingly, and partially in contrast to previous studies in adrenocortical cell cultures in vitro that have implicated TLR-signaling in the regulation of steroidogenesis (20), this study revealed no contribution of adrenocortical MyD88 to the systemic HPA activation or to the local immune-adrenal cross talk within the adrenal microenvironment in LPS-induced inflammation. On the other hand, our findings with these Mx1…”
Section: Discussioncontrasting
confidence: 99%
“…Surprisingly, and partially in contrast to previous studies in adrenocortical cell cultures in vitro that have implicated TLR-signaling in the regulation of steroidogenesis (20), this study revealed no contribution of adrenocortical MyD88 to the systemic HPA activation or to the local immune-adrenal cross talk within the adrenal microenvironment in LPS-induced inflammation. On the other hand, our findings with these Mx1…”
Section: Discussioncontrasting
confidence: 99%
“…TLR4 is expressed on human adrenocortical cells, and it is involved in immuneneuroendocrine crosstalk (Zacharowski et al, 2006). LPS directly stimulates cortisol secretion by NCI-H295 cells (Vakharia and Hinson, 2005), and IL-6 and IL-8 expression by human adrenocortical cells (Kanczkowski et al, 2009). We found significant underexpression of TLR4 in ACCs in two studies (Giordano et al, 2009;To¨mbo¨l et al, 2009) and confirmed TLR4 expression changes by QRT-PCR (data not shown).…”
Section: Bacterial Lipopolysaccharide (Lps) Recognition Via Toll-likesupporting
confidence: 80%
“…Both fatty acids have been found to be good precursors of cyclooxygenase-derived PG in fish (Bell et al 1994a, Ganga et al 2005. In turn, cyclooxygenase-derived PG have been shown to increase in vitro cortisol release in interrenal tissue of female frogs during ovulation (Gobbetti & Zerani 1993) and in human adrenal cells as well (Vakharia & Hinson 2005). Interestingly, DHA stimulation of ACTH-induced cortisol production was lower than that caused by EPA or ARA.…”
Section: Discussionmentioning
confidence: 99%